Kemampuan Sosialisasi Anak Prasekolah: Sebuah Studi Pentingnya Peran Orang Tua dalam Memberikan Stimulasi Sosialisasi pada Anak - Anita Mukharis; Umi Aniroh; Umi Setyoningrum (Jurnal Keperawatan, 2019)
Abstrak. Kemampuan sosialisasi merupakan kemampuan anak dalam beradaptasi dengan dunia sosial yang lebih luas. Salah satu faktor yang mempengaruhi kemampuan sosialisasi anak prasekolah adalah peran orang tua. Tujuan dari penelitian ini untuk mengetahui hubungan peran orang tua dalam stimulasi sosialisasi dengan kemampuan sosialisasi anak prasekolah. Desain penelitian ini adalah descriptive correlation dengan pendekatan cross sectional. Populasi pada penelitian ini adalah orang tua dan anak prasekolah. Sampel sebesar 105 orang dengan teknik proportional random sampling. Pengumpulan data menggunakan kuesioner. Analisis data menggunakan chi square (α=0,05). Hasil penelitian menunjukkan peran orang tua dalam kategori baik sebanyak 66 orang (62,9%). Kemampuan sosialisasi anak paling banyak pada kategori sedang, yaitu 45 orang (42,9%). Ada hubungan peran orang tua dalam stimulasi sosialisasi dengan kemampuan sosialisasi anak prasekolah dengan nilai p= 0,001. Diharapkan orang tua memberikan stimulasi terutama pada aspek sosialisasi untuk mengoptimalkan kemampuan sosialisasi anak. Abstract. Socialization ability is the ability of children to adjust to the wider social world. One of the factors that affect social ability is the role of parents. The aim of this study was to determine the correlation between the role of parents in social stimulation and social ability on preschool age. This study was a descriptive correlation study with cross-sectional approach. The population in this study was all students and parents. The samples were 105 parents and students using proportionate random sampling. The instrument about the role of parents in social stimulation and social skills on preschool age children was measured by using questionnaires. Data analysis used chi square test (α = 0.05). The results showed that the role of parents in social stimulation on preschool age children was in good category as many as 66 people (62,9%). The results showed social ability on preschool age children was in medium category as many as 45 people (42.9%). And good category as many as 34 people (34,3%). There was a correlation between the role of parents in social stimulation and social ability on preschool age children withp-value =0,001.Based on the results, parents are expected to give stimulation especially on socialization aspect for children to optimalize social ability of children.